A Digital Signature Scheme Based on MST3 Cryptosystems. (20th May 2014) - Hong, Haibo; Li, Jing; Wang, Licheng; Yang, Yixian; Niu, Xinxin
Abstract : As special types of factorization of finite groups, logarithmic signature and cover have been used as the main components of cryptographic keys for secret key cryptosystems such as PGM and public key cryptosystems like M S T 1, M S T 2, and M S T 3 . Recently, Svaba et. al proposed a revised M S T 3 encryption scheme with greater security. Meanwhile, they put forward an idea of constructing signature schemes on the basis of logarithmic signatures and random covers. In this paper, we firstly design a secure digital signature scheme based on logarithmic signatures and random covers. In order to complete the task, we devise a new encryption scheme based on M S T 3 cryptosystems.